Pengembangan Media AR SIKAYA Berbasis Assemblr Edu pada Mapel IPAS Kelas IV - Noviani, Nur Allya; Putra, Galih Mahardika Christian (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
This research aims to develop, validate the feasibility, and test the effectiveness of augmented reality learning media based on Assemblr Edu to improve student learning outcomes. This research uses an RnD approach with the Borg and Gall model. Data was collected through tests (pretest and posttest), observation, interviews, questionnaires, and documentation. Validation from material and media experts was 91.66% and 89.00% respectively with very feasible criteria. The pretest and posttest data were normally distributed. The t test results show a score of 0.00 < 0.05 so that H₀ is rejected and Ha is accepted. The n-gain test results show a score of 0.5882 in the medium category. Responses from teachers and students also showed positive responses. The conclusion of this research is that the SIKAYA learning media has been successfully developed, is very feasible, and is effectively applied to science subjects.